Kelvin Probe Force Microscopy From Single Charge Detection to Device Characterization (Springer Series in Surface Sciences,, 2018)
This book provides a comprehensive introduction to the methods and variety of Kelvin probe force microscopy, including technical details. It also offers an overview of the recent developments and numerous applications, ranging from semiconductor materials, nanostructures and devices to sub-molecular and atomic scale electrostatics. In the last 25 years, Kelvin probe force microscopy has developed from a specialized technique applied by a few scanning probe microscopy experts into a tool used by numerous research and development groups around the globe. This sequel to the editors' previous volume "Kelvin Probe Force Microscopy: Measuring and Compensating Electrostatic Forces," presents new and complementary topics. It is intended for a broad readership, from undergraduate students to lab technicians and scanning probe microscopy experts who are new to the field.